Hadith #5787 - Sahih Muslim - Wathla bin al-'Asqa' (Sahih Muslim)
I heard Allah’s Messenger (ﷺ) as saying: Verily Allah granted eminence to Kinana from amongst the descendants of Isma’il, and he granted eminence to the Quraish amongst Kinana, and he granted eminence to Banu Hashim amonsgst the Quraish, and he granted me eminence from the tribe of Banu Hashim.
Grade: Sahih